Bisphenol S impairs blood functions and induces cardiovascular risks in rats - Sanghamitra Pal; Kaushik Sarkar; Partha Pratim Nath; Mukti Mondal; Ashma Khatun; Goutam Paul (Toxicology Reports, 2017)
Bisphenol S (BPS) is an industrial chemical which is recently used to replace the potentially toxic Bisphenol A (BPA) in making polycarbonate plastics, epoxy resins and thermal receipt papers. The probable toxic effects of BPS on the functions of haemopoietic and cardiovascular systems have not been reported till to date. We report here that BPS depresses haematological functions and induces cardiovascular risks in rat. Adult male albino rats of Sprague-Dawley strain were given BPS at a dose level of 30, 60 and 120 mg/kg BW/day respectively for 30 days. Red blood cell (RBC) count, white blood cell (WBC) count, Hb concentration, and clotting time have been shown to be significantly (*P < 0.05) reduced in a dose dependent manner in all exposed groups of rats comparing to the control. It has also been shown that BPS increases total serum glucose and protein concentration in the exposed groups of rats. We have observed that BPS increases serum total cholesterol, triglyceride, glycerol free triglyceride, low density lipoprotein (LDL) and very low density lipoprotein (VLDL) concentration, whereas high density lipoprotein (HDL) concentration has been found to be reduced in the exposed groups. BPS significantly increases serum aspartate aminotransferase (AST), alanine aminotransferase (ALT) and alkaline phosphatase (ALP) activities dose dependently. Moreover, serum calcium, bilirubin and urea concentration have been observed to be increased in all exposed groups. In conclusion, BPS probably impairs the functions of blood and promotes cardiovascular risks in rats. Keywords: Bisphenol S, Red blood cell count, White blood cell count, Clotting time, LDL cholesterol, HDL cholesterol, Cardiovascular risks